An Intersectionality-Based Policy Analysis Examining the Complexities of Access to Wild Game and Fish for Urban Indigenous Women in Northwestern Ontario - Phillipps, Breanna; Skinner, Kelly; Parker, Barbara; Neufeld, Hannah Tait (Frontiers in Communication, 2022)
The destruction of Indigenous food systems is a direct consequence of the settler-colonial project within Canada and has led to decreasing access to Indigenous foods, disproportionate rates of food insecurity and disconnection from Indigenous food systems and environments. We interviewed Indigenous women, non-Indigenous staff of Indigenous-serving organizations, and policymakers (i.e. those who develop, interpret, or implement wild food policy) to explore how the policy context has impacted Indigenous women and their communities’ experiences of accessing Indigenous foods in urban northwestern Ontario. We applied an Intersectionality-Based Policy Analysis (IBPA) Framework to shape our research questions and guide the thematic analysis of the data. We found that stakeholder groups had differing understandings of the issue of accessing wild foods and Indigenous food security and their actions either supported or disrupted efforts for access to wild food to promote food security or Indigenous Food Sovereignty. Policymakers cited necessary barriers to promote food safety and support conservation of wildlife. Staff of Indigenous-serving organizations approached the issue with consideration of both Western and Indigenous worldviews, while Indigenous women spoke about the ongoing impacts of colonial policy and government control over their lands and territories. The main policy areas discussed included residential school policy, food regulation, and natural resource regulation. We also investigated community-level strategies for improvement, such as a wild game license. Throughout, we tied the colonial control over ‘wildlife’ and the Western food safety discourse, with infringements on Indigenous Food Sovereignty, experiences of racism in food settings and on the land, as well as with broad control over Indigenous sovereignty in Ontario. This work contributes to an increased understanding of how Western discourses about health, food, and the environment are perpetuated through systemic racism in government policy and reiterated through policymakers' views and interpretations or actions. Government institutions must develop culturally safe partnerships with Indigenous leaders and organizations to facilitate a transfer of power that can support Indigenous Food Sovereignty.